Pengaruh Good Corporate Governance Dan Pergantian Auditor Terhadap Integritas Laporan Keuangan - Tsania Jaza Safara; Annisa Nurbaiti (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Companies in the raw goods sector have an important role for Indonesia, because they are one of the sectors that can revive the economy in Indonesia after the Covid-19 case. Several companies listed on the Indonesia Stock Exchange in preparing and presenting their financial reports do not apply financial report integrity so that the information contained therein is invalid and is certainly an act of manipulating financial reports. Therefore, financial reports must be prepared and presented in accordance with conditions that reflect what is happening in a company or have integrity so that later the information contained in them can become a reference for users of financial reports. The purpose of this research is to determine the influence of Good Corporate Governance and changing auditors on the integrity of financial reports. The company objects are raw goods sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period with a sample size of 104 companies. The software used is Eviews 12.